ANALYSIS OF INTERPRETATION ABILITY AND MATHEMATICAL DISPOSITION BASED ON STUDENTS' LEARNING MOTIVATION - Nursyahidah, Silmi; Supratman, Supratman; Dewi, Sinta Verawati (Universitas Tanjungpura, 2025)
This study examines students' mathematical interpretation abilities and dispositions based on their learning motivation levels (high, medium, and low). Employing a qualitative approach with an exploratory method, this research collected data through interpretation ability tests, mathematical disposition and learning motivation questionnaires, and interviews to explore students' perceptions. Data analysis was conducted using the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. This study, conducted at SMP Negeri 1 Kadugede in class VII K, found characteristic differences based on motivation levels. Students with high motivation demonstrated enthusiasm, resilience, and optimism in mathematics, as well as comprehensive understanding, good representational abilities, and sound conclusion drawing, although their written answers were sometimes inaccurate. Students with medium motivation showed varied achievements, generally possessing sufficient self-confidence, perseverance, interest, and curiosity, capable of understanding problems, representing information, and drawing conclusions, although the accuracy of their writing and the scope of problems solved were still limited. Meanwhile, students with low motivation experienced difficulties in understanding problems, especially complex ones. In conclusion, learning motivation plays a crucial role in strengthening interpretation abilities and forming positive mathematical dispositions, potentially improving student achievement and active participation in mathematics learning.